Discourse Analysis of Directive Speech Acts in the Exclusive Interview “Prabowo Subianto Speaks for Indonesia” on TVOne’s Kabar Pagi Program: A Pragmatic Perspective - Eva Eri Dia; Mohammad Fithr Alfin Niam (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
Directive speech act is a form of utterance that is intended by the speaker to make an influence so that the speech partner performs an action. The object that the researcher studied was the exclusive interview video of Prabowo Subianto Bicara untuk Indonesia aired on TV and also available on YouTube TvOne. In this study of directive speech act analysis, researchers used descriptive qualitative method with pragmatic discourse review. The objectives of this study are to: (1) Identify directive speech acts in Prabowo Subianto's exclusive interview for Indonesia on Kabar Pagi TvOne (2) Analyze directive speech acts in Prabowo Subianto's exclusive interview for Indonesia on Kabar Pagi TvOne. This resulted in the findings of directive speech acts including: the directive speech acts of begging, requesting, giving orders, demanding, and prohibiting. This research focuses on the types and functions of directive speech acts found in the exclusive interview video of Prabowo Subianto 'Speaking for Indonesia'. The types of directive speech acts consist of words, phrases, clauses, or sentences. The data collection method uses observation and note-taking. The research process includes the analysis of directive speech acts found in the exclusive interview of Prabowo Subianto 'Speaking for Indonesia', as follows: (1) the author listens to and watches the exclusive interview on YouTube; (2) the author observes and notes the directive speech acts found in the exclusive interview on YouTube, https://youtu.be/pm7o4pGnB4g?si=6tWXQG-_uoTmXN_W; and (3) the author categorizes the directive speech acts found in the exclusive interview on YouTube. Speech has various types and is used for different reasons. Moreover, speaking during an interview has various practical reasons. When analyzed based on pragmatic studies, there are indeed many types of speech. One type is directive speech, where the speaker asks the interlocutor to do what the speaker requests. Directive speech acts dominate the interview.